Survival Rate Prediction of Head Injury Patients with Peripheral Oxygen Saturation - Nurma Afiani; Abdul Qodir; Wiwit Widyawati; Intan Purnama (Jurnal Ilmu dan Teknologi Kesehatan, 2021)
Good management of head injuries can improve patient survival. Examination of peripheral oxygen saturation (SpO2) is a procedure performed at the primary survey. This study aims to predict the survival rate of head injury patients with the SpO2 value. The method used was a prospective study with a cohort design. Samples were head injury patients who came to the ER without comorbidities. The instruments used were the Revised Trauma Score (RTS) and Oximetry. Patients who arrived at the ER were measured for their SpO2 levels, treated according to SOP, and 6 hours later, the survival rates were assessed. The sampling technique used was purposive sampling. The statistical test used is Somers’d Correlation Test. The sample consisted of 46 head injury patients with SpO2 in a good category of 30 (65.2%) and good survival of 32 (69.6%). SpO2 had a strong correlation with survival (p = 0.00; r = 0.846; RR = 8.16). Patients with good SpO2 were 8.16 times more survive than others. Low SpO2 can be used as an early indicator of tissue hypoxia and related to mortality. The ER nurse should be concerned about the patient's oxygen saturation and ensure that the SpO2 level is in the 95% -100% range.